Development of Self-Help Lifting Pads for Elderly People with Difficulty in Sitting Up - Manatee Jitanan; Kamphon Saeng-iam; Ekathai Wirojsakunchai; Kuanchai Kakaew; Usanee Lalitpasan (Designs)
As individuals age, physiological changes can make it increasingly difficult to sit up unassisted. This study aimed to develop ergonomic self-help lifting pads to aid elderly individuals. The first phase involved constructing the pads and a needs assessment with elderly participants and caregivers to survey the physical dimensions and requirements for the design. The second phase focused on cost, engineering, and usage efficiency. Cost efficiency was analyzed using descriptive statistics, engineering efficiency was assessed through testing seat cushion, force reduction, and electrical safety, and usage efficiency was evaluated with participants aged 40 to 50 years. Results from the first phase indicated that the pads should be at least 53.15 cm wide and 153 cm long, with a need for relaxation and affordability. In the second phase, prototype pads were developed according to these specifications. A cost analysis showed that while the manual pad was more expensive than comparable products, the other variants were more cost-effective. Engineering tests confirmed that the cushions met ASTM D3574 standards and that the electrical components conformed to IEC 60335 standards. Usage efficiency ratings were the highest for the massage system pad. Participant feedback indicated longer pads, more convenient controls, and increased cushion comfort, guiding the development of the second version.